2017
DOI: 10.1177/1053451217712953
|View full text |Cite
|
Sign up to set email alerts
|

Punishing the Vulnerable: Exploring Suspension Rates for Students With Learning Disabilities

Abstract: Students with learning disabilities are suspended at disproportionate rates in schools. Although research has shown the ineffectiveness of suspension as a disciplinary tool, school administrators continue to use it to combat behavior infractions. This column presents a review of the literature on suspension for students with learning disabilities, its impact on their academic achievement, and sociodemographic factors that put students with learning disabilities at risk for suspension. Implications are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Brobbey (2018) synthesized the discipline literature pertaining to SWDs and reported that students with learning disabilities accounted for 11% of the population but 20% of all suspensions. The study also reported that (a) students with learning disabilities were more likely to be suspended than students without learning disabilities and (b) minority students with learning disabilities were more likely to be suspended than White students with learning disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Brobbey (2018) synthesized the discipline literature pertaining to SWDs and reported that students with learning disabilities accounted for 11% of the population but 20% of all suspensions. The study also reported that (a) students with learning disabilities were more likely to be suspended than students without learning disabilities and (b) minority students with learning disabilities were more likely to be suspended than White students with learning disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to racial disparities, studies have also highlighted discrepancies in discipline practices for males (e.g., Bradshaw et al, 2010), students of low socioeconomic status (e.g., Petras et al, 2011), and students labeled with disabilities (e.g., Brobbey, 2018;Sullivan et al, 2013). Intersectionality (i.e., intersecting forms of oppression, exclusion, and erasure; see Annamma et al, 2018;Blake et al, 2017) refers to the compounding experiences of social injustice for students at the intersections of these groups (Artiles, 2011).…”
mentioning
confidence: 99%
“…Students who are CLD with disabilities are more susceptible to high rates of disciplinary exclusions such as suspensions and expulsions (Brobbey, 2018; Vincent, Randall, Cartledge, Tobin, & Swain-Bradway, 2011; Whitford & Addis, 2017) and are at greater risk for exclusion from the general education classroom and school failure due to academic frustration (Brobbey, 2018). For CLD families of students with disabilities, there might be a disconnection between the school culture and the home or community culture, meaning that there might be differing views about school-based behavior management methods that are not consistent with home approaches (Hill, 2010).…”
Section: Engaging With Behavior Strategiesmentioning
confidence: 99%